Heterodoxias da arte de curar portuguesa de oitocentos : o caso da homeopatia - Araújo, Yann Loic Macedo de Morais (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This paper refers to the case-study of one of the therapeutic alternatives to the classical medicine, surgery and pharmacy of the Portuguese 19th century - homeopathy. We start by understanding the context in witch it emerged as a sick-people medicine. We then describe the process of its reception, introduction and divulgation both by laypeople in medicine and physicians, at a personal and an institutional level. We seek therefore to evoke the history of a medical-pharmaceutical heterodoxy that was, for a large period of the Portuguese 19th century, an actual threat to the official medicine.